Journalism, media, and technology trends and predictions 2021 - Newman, N (Reuters Institute for the Study of Journalism, 2021)
This annual Reuters Institute predictions report looks at the key trends that will impact media in 2021. It looks at how business models will be affected by Covid-19 and at the emergence of new hybrid in-person and remote newsrooms. The report explores likely action by tech platforms in clamping down on false information - and attempts by government to regulate the internet over harmful and misleading content. It also looks at how journalism is being affected by the next wave of technological disruption from AI-driven automation, big data, and new visual and voice-based interfaces.